Carbon capture potential of 3D printable concrete with self-curing additives - Bawarith, Nuran Khalid A (Nanyang Technological University, 2024)
This research aims at studying carbon capture potential in 3D printable concrete by using Polyethylene Glycol 6000 (PEG) as the self-curing additive. 3D printable concrete samples are prepared with different percentages of PEG (0%, 1 %, 2 % and 3%). The mix is subjected to two printing processes. The first printing process includes standard 3D concrete printing (3DCP), the passive capturing of carbon dioxide (CO2) from the surrounding environment while printing. The second printing process uses a custom made in-line static mixer for CO2-steam integrated printing. The 3D-printed concrete’s mechanical strength was evaluated through compression and flexural testing performed after 7 days and 28 days of curing. The cured samples are subjected to Thermogravimetric Analysis (TGA) to estimate the amount of carbon uptake in each sample. Moreover, this study examines the rheological properties of concrete mixes with varying PEG percentages compared to an Ordinary Portland Cement (OPC) reference, utilizing the Bingham Model to compute quasi-static yield stress, dynamic yield stress, and plastic. For standard 3DCP, findings suggest that PEG enhances early strength development and carbon capture, with an optimal concentration of 2% PEG for maximizing compression strength. Additionally, PEG improves flowability and extrudability, benefiting complex geometries. For CO2-steam integrated printing findings show that PEG is effective in carbon capture and enhances early and subsequent strength development in flexural tests. This is likely due to its moisture retention properties, which also impact yield stresses and viscosity. The optimal PEG concentration, peaking at 2%, maximizes compression strength.